Small But Healthy: An Adaptive Response in Baduy Children - Rohmatullayaly, Eneng Nunuz; Shelvie Raffiza Nasihin; Kharisma Nurinsani Maulidinda; Sinta Septi Pangastuti; Tetri Widiyani (HAYATI Journal of Biosciences, 2025)
Life history explains natural selection, resulting in phenotypic plasticity that can be studied through the growth pattern (growth rate and body size). The Baduy People, one of the indigenous peoples in Indonesia, exhibit prolonged growth, a slow growth rate, a low peak growth spurt, and small adult size as an adaptation to challenging biocultural conditions. The life history trade-offs of the Baduy People are demonstrated by ontogenetic allometry, which synchronizes between skeletal growth and future reproduction. The study aims to characterize the growth of Baduy children aged 0-5 years with more precise ‘tracking’ of developmental plasticity. We collected anthropometric data (body height-BH, body weight-BW, head circumference-HC, body mass index-BMI) using a cross-sectional method from 118 girls and 97 boys aged 0-5 years across 24 Baduy Luar hamlets. Data were analyzed with Generalized Additive Models for Location, Scale, and Shape (GAMLSS) in R version 4.2.1. Nutritional statuses were categorized based on the BMI z-score. The growth pattern showed a decline in growth rate after birth until 2 or 3 years, but the body size increased yearly. The body size (BH and BW) of Baduy children is lower than the Indonesian National Synthetic Growth Charts (INSGC), but most of them have a good nutritional status (>80%). This finding is consistent with the "small but healthy" hypothesis: a small body is an advantageous evolutionary strategy for energy efficiency and maximizing growth potential in challenging biocultural conditions.